A complex patchwork of magma bodies that fed the Bishop Tuff supereruption (Long Valley Caldera, CA, United States): Evidence from matrix glass major and trace-element compositions - Gualda, Guilherme A. R.; Ghiorso, Mark S.; Hurst, Aaron A.; Allen, Madeline C.; Bradshaw, Richard W. (Frontiers in Earth Science, 2022)
For more than 40 years, the Bishop Tuff has been the archetypal example of a single, zoned magma body that fed a supereruption. Early-erupted material is pyroxene-free and crystal poor (<20 wt. %), presumably erupted from the upper parts of the magma body; late-erupted material is orthopyroxene and clinopyroxene-bearing, commonly more crystal rich (up to 30 wt. % crystals), and presumably tapped magma from the lower portions of the magma body. Fe-Ti oxide compositions suggest higher crystallization temperatures for late-erupted magmas (as high as 820 °C) than for early-erupted magmas (as low as 700 °C). Pressures derived from major element compositions of glass inclusions led Gualda & Ghiorso (2013, CMP) to suggest an alternative model of lateral juxtaposition of two main magma bodies – each one feeding early-erupted and late-erupted units. Chamberlain et al. (2015, JPet) and Evans et al. (2016, AmMin) recently disputed this interpretation. We present a large dataset of matrix glass compositions for 227 pumice clasts that span the stratigraphy of the deposit. We calculate crystallization pressures based on major-element glass compositions using rhyolite-MELTS geobarometry and crystallization temperatures based on Zr in glass using zircon saturation geothermometry. Additionally, we apply the same methods to 1538 major-element and 615 trace-element analyses from Chamberlain et al. (2015). The results overwhelmingly demonstrate that the variations in crystallization temperature and pressure are not consistent with vertical stratification of a single magma body. All crystallization pressures and temperatures are very similar, with modes of ~150 MPa and ~730 °C. Our results strongly support lateral juxtaposition of three main magma bodies. Magmas represented by smaller stratigraphic units studied by Chamberlain et al. (2015) crystallized at similar pressures as the main bodies, which suggests coexistence of larger and smaller magma bodies at the time of eruption. We compare our findings with results for other very large eruptions and supereruptions. We argue that supereruptions typically mobilize a complex patchwork of magma bodies that reside within specific levels of the crust. These eruptions reveal the architecture of the crust during moments of high abundance of eruptible magma, unlike what we observe in the Earth today.